Characterization of bio-cement reinforced with eggshell composites / N. A. Sufiah M Razak ... [et al.] - M Razak, N. A. Sufiah; Ramli, Rosmamuhamadani; Mahat, M.M.; Osman, S.; Zakaria, M.N.; Yahaya, S.M. (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2024)
Eggshells are an interesting inorganic compound with a chemical composition and crystallographic structure similar to that of CaCO3. This study aims to acquire a better understanding of the use of eggshells, which are commercially incorporated into cement mixtures, to increase the mechanical strength of cement-eggshell composite. The cement mixture was prepared by incorporating different compositions (5, 10, and 15 wt.%) of eggshell powder. The raw eggshells were cleaned, crushed, dried, sieved into small pieces, and mixed with the cement according to the desired composition. Analysis of the eggshell powder showed similar peaks to CaCO3, indicating that eggshells can be used as a calcium source. The results indicated that the addition of 10 wt.% finely ground eggshell powder improved the compressive and flexural strength of the cement mix. It was also found that eggshell powder can potentially be used as a filler, as it exhibited the highest water absorption at 15 wt.%. The use of eggshells as a reinforcing component in environmentally friendly cement mixes has the potential to improve the environment by reducing waste, the need for conventional cement resources, and the pollution caused by excessive cement mining.